Análise do ângulo de rotação da coxa em indivíduos com síndrome da dor patelofemoral durante a subida de degraus - Kuriki, Heloyse Uliam [UNESP]; Azevedo, Fábio Mícolis de [UNESP]; Negrão Filho, Rubens de Faria [UNESP]; Alves, Neri [UNESP] (My University, 2012)
Introduction: The femur rotation can lead to increased pain in individuals with patellofemoral pain syndrome (PFPS). However, few studies are found in order to measure this rotation. Objective: Compare the angle of the femur rotation of patients with and without PFPS during stair climbing. Methods: Femur rotation was analyzed in 11 female volunteers with PFPS and 22 without PFPS using the Ariel Performance Analysis System for data acquisition and digitization, an algorithm for calculating the rotation and Student’s t-test for comparison of data, with 5% of significance. Results: Regarding external rotation, the PFPS group had a higher angle 8.86° (±7.6°) in relation to the control group 5.72° (±5.0°) (p=0.015). Conclusion: The results showed that individuals with PFPS presented a greater external rotation angle, what can be the factor that causes the pain, as further rotation leads to an increase in patellar pressure.

Introdução: A rotação no fêmur pode levar ao aumento da dor em indivíduos com síndrome dolorosa patelofemoral (SDFP). Entretanto, poucos estudos são encontrados com o objetivo de mensurar essa rotação. Objetivo: Comparar o ângulo de rotação do fêmur de indivíduos com e sem SDFP durante a subida de degraus. Métodos. Foi analisada a rotação do fêmur em 11 voluntárias com SDFP; e 22, sem SDFP, utilizando o Ariel Performance Analysis System para aquisição e digitalização dos pontos, um algoritmo para o cálculo da rotação e o teste “t” de Student, com significância de 5%, para comparação dos dados. Resultados: Quanto à rotação externa, o grupo SDFP apresentou maior rotação, 8,86°(±7,6°), em relação ao controle, 5,72°(±5,0°), (p=0,015). Conclusão: Verificou-se que indivíduos com SDFP apresentam maior ângulo de rotação externa de fêmur, o que pode ser o fator desencadeador da dor, já que uma maior rotação leva a um aumento da pressão patelar.
Analysis of the thigh rotation angle in individuals with patellofemoral pain syndrome during stair walking
Keywords: Hip; Patellofemoral pain syndrome; Kinematics; Rotation; Cinemática; Quadril Síndrome da dor patelofemoral; Rotação